(untitled) (KULT_online, 2016)
In African American Travel Narratives from Abroad: Mobility and Cultural Work in the Age of Jim Crow, Gary Totten sheds new light on black writers’ journeys, reading their travel texts as means to perform ‘cultural work’ and resist Jim Crow policies. His insightful analysis of the texts highlights their potential to construct new narratives of African American mobility and identity in the face of racial violence and discrimination.